Dinamika Tutupan Lahan di Kawasan Karst Kecamatan Gunem Kabupaten Rembang - Rina Sunia Setya; Erry Wiryani; Jumari Jumari (School of Postgraduate Studies, Diponegoro Univer, 2019)
Research on land cover change in the karst region is currently an important study as an indicator of evaluating global environmental changes. Karst area is a unique natural phenomenon on the surface of the earth because it has an important role in water conservation, CO2 absorption, and maintenance of biodiversity but is very vulnerable to damage due to human activities. The purpose of this study was to analyze changes in karst land cover in Gunem District, Rembang Regency, Central Java using satellite image data and GIS (Geographical Information System). The research method used is to compare three data on the distribution of land cover in 1997, 2008 and 2017 obtained from the interpretation of satellite image data. The results of the study are that land cover based on the results of the interpretation of satellite imagery is classified into four classes, namely fields / gardens, fields, built up land and water bodies. In the last 20 years the cover class of upland / garden land continues to experience a downward trend, while the built-up land cover class continues to increase. Changes in land cover in the karst area of Gunem Subdistrict during the period of 1997-2017 were influenced by factors of human activity which included population growth, housing needs, and supporting facilities. This result is expected to be a consideration in carrying out sustainable development planning and placing karst as a protected area.